1989
DOI: 10.1172/jci113945
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-induced critical point. Mechanism for electrical initiation of reentry in normal canine myocardium.

Abstract: The hypothesis was tested that the field of a premature (S2) stimulus, interacting with relatively refractory tissue, can create unidirectional block and reentry in the absence of nonuniform dispersion of recovery. Simultaneous recordings from a small region of normal right ventricular (RV) myocardium were made from 117 to 120 transmural or epicardial electrodes in 14 dogs. SI pacing from a row of electrodes on one side of the mapped area generated parallel activation isochrones followed by uniform parallel is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
190
2
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(201 citation statements)
references
References 40 publications
7
190
2
1
Order By: Relevance
“…This ''reentrant'' activity was possible because of the inhomogeneity in excitability that existed for a brief moment and was ''unmasked'' by the special stimulation protocol. Similar results have later been obtained ͑but with a single very strong stimulus͒ in intact hearts 12 and in isolated thin preparations of dog and sheep cardiac muscle, 13 where unidirectional block and reentry were induced by a similar stimulation pattern. ͑For an excellent description of the basic characteristics of reentry the reader is referred to the article by Gray and Jalife, appearing in this volume.͒ 14 A key requirement for the induction of reentry is the presence of unidirectional block.…”
Section: Introductionsupporting
confidence: 81%
“…This ''reentrant'' activity was possible because of the inhomogeneity in excitability that existed for a brief moment and was ''unmasked'' by the special stimulation protocol. Similar results have later been obtained ͑but with a single very strong stimulus͒ in intact hearts 12 and in isolated thin preparations of dog and sheep cardiac muscle, 13 where unidirectional block and reentry were induced by a similar stimulation pattern. ͑For an excellent description of the basic characteristics of reentry the reader is referred to the article by Gray and Jalife, appearing in this volume.͒ 14 A key requirement for the induction of reentry is the presence of unidirectional block.…”
Section: Introductionsupporting
confidence: 81%
“…These considerations led to the ULV hypothesis, which states that for a shock to successfully terminate VF, it must alter the transmembrane potential throughout the myocardium in such a way that the wavefronts of VF are halted, yet new wavefronts that can reinitiate VF are not induced (69). These realizations led to the development of the critical point theory of defibrillation, which suggested that reentry was initiated at the intersection of critical points of local field strength and tissue with critical levels of recovery (68,71).…”
Section: Critical Pointsmentioning
confidence: 99%
“…In many of the optical and electrical mapping studies that have attempted to determine the mechanism by which shocks give rise to action potentials that reinitiate VF, the shocks were not given during VF but during phase 2 or phase 3 of the action potential of paced rhythm (54,(71)(72)(73)(74). These shocks were observed to induce reentry that degenerated into VF by the creation of a critical point (Figure 12).…”
Section: Critical Pointsmentioning
confidence: 99%
“…11,12 Different meandering spiral patterns are also found in a RD model of flames. 13 Although some deviations from circular cores have been reported for yeast extracts 14 and neural tissue, 15,16 systematic experiments on noncircular tip trajectories are limited to the BZ reaction. In this system, tip trajectories can follow circles, hypocycles (outwardly pointing petals), epicycles (inwardly pointing petals), or a special kind of trochoid called prolate cycloid with lobes along a straight line.…”
Section: Introductionmentioning
confidence: 99%
“…23 Experimental evidence for this behavior is meager and limited to investigations of highly anisotropic heart muscles using multiple electrode mapping techniques. 15,16 However, these experiments lacked the necessary resolution to yield detailed tip trajectories.…”
Section: Introductionmentioning
confidence: 99%